The league of extraordinary gentlemen - Albert, Trevor; Murphy, Don, 1962-; Robinson, James Dale.; Norrington, Stephen; Connery, Sean.; Shah, Naseeruddin; Wilson, Peta.; Curran, Tony.; Townsend, Stuart, 1972-; West, Shane; Flemyng, Jason; Roxburgh, Richard; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2003)
A legion of superheroes, the likes of which mankind had never seen, must band together under the leadership of Allan Quartermain to save the world from "The Fantom" who is threatening to launch a global Armageddon.
Based upon the graphic novel by Alan Moore and Kevin O'Neill.
Videodisc release of the 2003 motion picture.
Special features: Full-length audio commentary (producers/ actors) ; full-length audio commentary (costume/makeup/ visual effects team) ; behind the scenes documentary ; 12 deleted scenes.
Director of photography, Dan Laustsen ; art director, Marco Bittner Rosser ... [et al.] ; edited by Paul Rubell ; music by Trevor Jones ; costume designer, Jacqueline West ; production designer, Carol Spier.
Sean Connery, Naseeruddin Shah, Peta Wilson, Tony Curran, Stuart Townsend, Shane West, Jason Flemyng, Richard Roxburgh, Max Ryan, Tom Goodman-Hill.
MPAA rating: PG13; for intense sequences of fantasy violence, language and innuendo.
Keywords: Heroes -- Drama; Armageddon -- Drama; Feature films; Films for the hearing impaired